MEG3 sponges miRNA-376a and YBX1 to regulate angiogenesis in ovarian cancer endothelial cells. Issue 2 (February 2023) - Li, Yize; Zhang, Lingling; Zhao, Yongmei; Peng, Hongyan; Bai, Wendong; Zhang, Nan
Abstract: Objectives: Recent studies have demonstrated maternally expressed gene 3 (MEG3) as a tumor suppressor across multiple malignancies. Meanwhile, the role of MEG3 in ovarian cancer needs further investigation. We aim to study the effects of MEG3 on angiogenesis in ovarian cancer and the underlying mechanisms. Methods: The transcript levels of MEG3 in ovarian cancer samples from the GEPIA database were analyzed and compared to those in normal samples. The effect of MEG3 on the tube formation ability was quantified in ovarian carcinoma-derived microvascular endothelial cells (ODMECs). Through sequence analysis, we identified miR-376a as a major candidate to bind to MEG3. A MEG3-miR-376a binding site was identified via genetic modulation methods. RAS p21 protein activator 1 (RASA1) was screened as a middle player to bridge the role of miR-376a and angiogenesis. The regulation between miR-376a and RASA1 was confirmed via a dual-luciferase reporter assay. Finally, the competition was explored between Y-box binding protein 1 (YBX1) and miR-376a in binding to MEG3. Results: MEG3 was significantly downregulated in ODMECs compared with normal ovarian endothelial cells. Overexpression of MEG3 led to reduced tube formation of ODMECs. The MS2 hairpin assay showed that MEG3 acted as a platform to sponge miR-376a. RASA1, a key suppressor of tube formation, was directly targeted by miR-376a. Further, MEG3 suppressed angiogenesis through the miR-376a/RASA1 axis in ODMECs. Finally, YBX1 and miR-376a were competitively bound to MEG3. Conclusion: This study uncovered a novel mechanism that MEG3 sponged miRNA-376a and YBX1 to regulate the expression of RASA1 and exert an effect on the angiogenesis of ovarian cancer.